(3GdMLIs - (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj, CHh Ydj,J (B377 (3g` s ((3GdYHGS Hf CMeO Hf CHj ehGS s)
(3ChdgG (B:s
(3JHJOF Hbhdg JYGdi (B" (3EfG ChMjfG Edjc ceG ChMjfG Edi fhM (B" s
(3BNQgG (B:s
(3hJfJgi Edi BNQ ShQI (B" (3GdRNQa (B" s
(3eLdO BNQ ef faS GdfSNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
(3TgjO Ydi (B(26) s
Keywords: (3GdbQGAGJ hGdJLhjOs